(untitled) (Colloquia Comparativa Litterarum, 2025)
The present article attempts to study the personality of Ivan Vazov as a perceiver of Western European literature. Vazov’s works are representative of the tendencies which started during the Bulgarian National Revival period, tendencies toward overcoming cultural backwardness and inclusion of Bulgarian literature in the European tradition. He devoted a great part of his literary and public activity to this cultural cause. In his body of work, Vazov accumulated the ideas of cultural catching up, distilled the best of the European experience, summarised it, and integrated it. The inclusion of Vazov’s works in the European literary tradition can be traced in the various modes of his communication with the national literatures of Western Europe – as a reader, translator, compiler, critic, editor, and author. Emphasising the Western influence in his work, he pointed out his models, constantly comparing himself to them, borrowing themes and motifs, genres and means of expression. Vazov managed to develop as an author of his own time – relevant to the native ideological and cultural context, but integrating the European literary achievements in his work.